2012
DOI: 10.1038/ijo.2012.200
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure in obese children with pseudohypoparathyroidism type 1a

Abstract: ContextPatients with pseudohypoparathyroidism type 1a (PHP-1a) develop early-onset obesity. The abnormality in energy expenditure and/or energy intake responsible for this weight gain is unknown.ObjectiveThe aim of this study was to evaluate energy expenditure in children with PHP-1a compared with obese controls.PatientsWe studied 6 obese females with PHP-1a and 17 obese female controls. Patients were recruited from a single academic center.MeasurementsResting energy expenditure and thermogenic effect of a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…Growth hormone deficiency, impaired lipolytic response of adrenaline (101) or decreased resting energy expenditure (106) contribute to the development of obesity in patients with mutations on the maternal allele of GNAS (23,107). Obesity is also a frequent feature in patients affected with acrodysostosis (16,90,108).…”
Section: Obesity/overweightmentioning
confidence: 99%
“…Growth hormone deficiency, impaired lipolytic response of adrenaline (101) or decreased resting energy expenditure (106) contribute to the development of obesity in patients with mutations on the maternal allele of GNAS (23,107). Obesity is also a frequent feature in patients affected with acrodysostosis (16,90,108).…”
Section: Obesity/overweightmentioning
confidence: 99%
“…Children with PHP1A and obesity show both decreased resting energy expenditure compared with controls with obesity and hyperphagic symptoms similar to those seen in BMI-matched controls with obesity 39,111,112 . In older (late infancy, adolescence and young adulthood) patients, this hyperphagic trait seems to abate 111 , and energy expenditure seems to improve to low-normal 113 .…”
Section: Obesity and Other Metabolic Issuesmentioning
confidence: 68%
“…In brief, PHP1A is caused by inactivating variants on the maternal allele of the GNAS gene within exons 1-13 (referring sequences NG_016194.1/NM_001077488.1 and LRG_1051), including both point mutations and rare gene rearrangements 16,23,27,41,45,86,88,97,112,122,[143][144][145][146][147][148] ( Supplementary Fig. 1b).…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…172 However, meal-induced thermogenesis, a response believed to require central melanocortin activation, tended to be lower in these adult PHP type 1a patients, 172 similar to what has been observed in children with PHP type 1a. 173 By contrast, two other studies performed in children with PHP type 1a showed a profound reduction in serum norepinephrine 174 or lower resting energy expenditure 173 as compared with obese controls. Taken in context, these studies imply that metabolic differences may be more significant in children than in adults with PHP type 1a, and are consistent with the observation that the obesity in PHP type 1a is more severe in the pediatric than in the adult population.…”
Section: Multiple Hormone Resistance In Pseudohypoparathyroidism Type 1amentioning
confidence: 85%